Occupational diseases among healthcare and social workers in 2009-2016 - Beata Świątkowska; Wojciech Hanke (Nofer Institute of Occupational Medicine, 2018)
Background The aim of the paper is to present statistical data on the occurrence of occupational diseases among healthcare and social workers in Poland in 2009-2016. Material and Methods All cards certifying that a case of occupational disease had been diagnosed in a patient belonging to this occupational group, received by the Central Register of Occupational Diseases, served as the basis of the study. Data is presented in absolute numbers and incidence rates. In the analysis, disease categories, voivodships and occupations were taken into account. Results In 2009-2016, as many as 1462 cases of occupational diseases were diagnosed for healthcare workers. In 2016, the number of cases was 42.6% lower than in 2009. Mean annual incidence rate in these years was 26.3 cases per 100 thousand workers. The most frequent were: infectious and parasitic diseases (64.8% of cases), peripheral nervous system diseases (9.6%), dermal diseases (8.9%), locomotor (8.3%), and chronic vocal organ disorders (3.2%). Among infectious or parasitic diseases, the most cases were viral hepatitis (56%) and tuberculosis (39%). Almost every second case of occupational disease in healthcare workers was detected in the nurses (47.8%). Conclusions The incidence of occupational diseases in total and in the most frequent categories continued to decrease. One of the reasons for the decline is the improvement of working conditions resulting from the application of more modern instruments and apparatus as well as greater knowledge of the risks and the use of appropriate procedures. Med Pr 2018;69(5)